Money-income and credit-income relationships during the pre- and the post-liberalization periods: evidence from Malaysia - Azali, M.; Matthews, K.G.P. (Taylor and Francis Group, 1999)
Using the Bernanke's contemporaneous structural VAR, this paper investigates the role of money and credit in the monetary transmission mechanism during the pre- and post-liberalization periods in Malaysia. During the pre-liberalization period where credit and interest rates were regulated, the evidence supports the dominance of bank credit shocks over money shocks in explaining the output variability. After the liberalization of financial market, however, money as well as credit innovations were proven to make significant contribution to the output fluctuation.